Effect Of Red Amber (Amaranthus Tricolor L.) Extract on Soil-Transmitted Helminth Worm Egg Morphology as a Substitute for 2% Eosin - Telambanua, Arniat Christiani; Sri Handayani (Rajaki of Tulip Medika Publisher, 2025)
The prevalence of worm disease in Indonesia is around 45-65%. The cause of worm infections that are still common in Indonesia is intestinal nematodes. The intestinal nematode group inhabits the digestive tract and is classified within the Soil-Transmitted Helminths group. This group requires contact with warm, moist soil to reach an infectious form. Clinically important soil-transmitted helminth species that infect humans are Ascaris Lumbricoides (roundworm), Trichuris Trichiura (whipworm), Anylostoma Duodenale, and Necator Americanus. This study aimed to determine the effect of red spinach extract (Amaranthus tricolor L.) on the morphology of soil-transmitted helminth eggs as a substitute for 2% Eosin. The research method used was experimental research, and the design used was Statistical Group Comparison. The results of this study are that red spinach extract (Amaranthus tricolor L.) can be used as an alternative coloring in the microscopic examination of soil-transmitted helminth worm eggs. A concentration of 1:1 shows the optimal concentration that can color Soil Transmitted Helminth worm eggs.